Culture of Interfaith Tolerance in Multicultural Communities In Mbawa Village, Donggo District, Bima Regency - Kamaruddin, Syamsu (Tamaddun Life, 2024)
The people of Mbawa Village, Donggo Subdistrict, Bima Regency, West Nusa Tenggara, consist of various monotheist religions, such as Islam, Catholicism and Protestantism. With a pluralistic background, the people of Mbawa Village are able to maintain a culture of tolerance that has been passed down by their ancestors. This research aims to explore and analyse the culture of interfaith tolerance in Mbawa Village, Bima Regency, West Nusa Tenggara. Mbawa Village is an example of a multicultural society inhabited by various religious groups that live side by side in harmony. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that the culture of interfaith tolerance in Mbawa Village is reflected in various aspects of community life, such as religious rituals, customs, and daily interactions. Factors that support interfaith tolerance include the existence of social norms that respect diversity, positive interfaith interactions, and the role of religious leaders and community leaders in promoting peace and harmony. In addition, awareness of the importance of inter-religious harmony and a deep understanding of the teachings of each religion also strengthen the culture of tolerance in Mbawa Village. This research makes an important contribution to understanding the cultural dynamics of interfaith tolerance in multicultural societies, particularly in the West Nusa Tenggara region. The implications of these findings can serve as a reference for policy makers and related parties to develop more effective strategies in promoting peace and inter-religious harmony in Indonesia.